KAJIAN KUALITAS LINGKUNGAN PERMUKIMAN di DAERAH PINGGIRAN KOTA (KASUS di DESA NGESTIHARJO, KECAMATAN KASIHAN, KABUPATEN BANTUL, PROVINSI DI YOGYAKARTA) - , Prittaningtyas Ekartaji, Prof Dr. H.Hadi Sabari Yunus.,M.A.,DRS (UTRECHT) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was conducted to study the quality of settlement environment in urban periphery with Desa Ngestiharjo, Kecamatan Kasihan, Kabupaten Bantul as locus of study. The objectives of this research were (1) to analyze the distribution of environmental quality of the settlements in Desa Ngestiharjo